Technology evolution and long waves: Investigating their relation with spectral and cross-spectral analysis - Eirini Ozouni; Constantinos Katrakylidis; Grigoris Zarotiadis (Journal of Applied Economics, 2018)
The present paper is an empirical exercise that contributes to the debate on whether long-lasting cyclical economic development can be viewed as a deterministic phenomenon or a stochastic process. First, we search for longer lasting, periodically reappearing cycles of GDP per capita in four countries: USA, UK, Germany and France. Second, based on theoretical arguments that stress applied knowledge as a significant driving force, we test its dynamic interrelationship with these countries' economic performance by applying spectral and cross-spectral methodologies. We confirm the existence of periodical long waves both in terms of GDP per capita as well as of applied knowledge. Moreover, we find strong interrelations between them and modest evidence for which is the leading force in the long term.
Keywords: 330; applied research; cross-spectral analysis; Long waves